The Camera Phone in the Concert Space: Live Music and Moving Images on the Screen - Glitsos, Laura (Liverpool University Press Online, 2018)
In this article, I argue that screen relations have profoundly redirected affective and aesthetic strategies of live music experience to culminate in a complex relationship with camera phone technology that is characterised by feelings of possessiveness, a sense of control over narrativising one’s experience, and new sentiments towards concert community. I examine the ways in which the camera phone produces new and alternative viewing pleasures because of the way the technology can structure new narratives of the concert experience. However, I note the conflicting, and at times very negative sentiments, emerging from the ubiquity of the camera phone. In particular, I examine the disruption of social viewing practices by those holding up the device or by the brightness of the display that distracts other viewers from the stage, as well as the ways in which the camera phone has been constructed in popular discourse as a technology which detracts from living experience ‘in the moment’.